The knowledge of food heritage identity in Klang Valley, Malaysia - Md Ramli, Adilah; Mohd Zahari, Mohd Salehuddin; Abdul Halim, Nurhasmilaalisa; Mohamed Aris, Mohammed Haidrin (Elsevier, 2016)
Classical and traditional food was closely associate with food heritage has become a significant role in the life of society and also to an individual. A study examines how far Malaysian knows about their food heritage identity. A total of 500 respondents located in Klang Valley participate in this study. Findings showed that food heritage been defined as traditional food. There is a significant relationship between genders with the definition of food heritage; the association of food heritage questions. Overall finding revealed that respondent understand the definition, the criteria's and type of traditional food associated with food heritage.